Optimizing Wordwall Based Gamified Learning in Teaching Writing of Procedure Text - Mahera Satrio Wicaksono; Inayatul Ulya (FKIP, Universitas Palangka Raya, 2026)
This study investigated the implementation of Wordwall-based gamified learning in teaching writing of procedure text among tenth graders at SMA Negeri 1 Wiradesa. The research aimed to describe how Wordwall was implemented in the classroom and to identify its strengths and weaknesses in supporting students’ writing activities. This study employed a descriptive qualitative research design involving 30 tenth-grade students and one English teacher as the research participants. The data were collected through classroom observations, interviews, questionnaires, and students’ writing tests. The findings revealed that the implementation of Wordwall created a more interactive, enjoyable, and student-centered learning atmosphere. The gamified activities increased students’ motivation, classroom participation, vocabulary mastery, and understanding of the generic structure and language features of procedure text. Students also became more confident and actively involved during writing activities. However, several challenges were identified, including unstable internet connection, limited time allocation, and difficulties experienced by some students in understanding game instructions and writing accurately. This study aimed to describe the implementation of Wordwall-based gamified learning in teaching procedure text writing and to identify its strengths and weaknesses among tenth-grade students at SMA Negeri 1 Wiradesa.